Analysis of Beginning Reading Ability in Lower Grade Elementary School Students - Estuning Dewi Hapsari; Dedy Richi Rizaldy; Kodrat Eko Putro Setiawan; Aviv Herawati (Lingeduca: Journal of Language and Education Studies, 2024)
Beginning reading must be mastered by students. This is because reading ability will influence the learning process and achievement. This research aims to determine the reading difficulties experienced by students using the phonics method. The method used is a case study. In this research, there are five stages, namely determining the problem, designing and research instruments, collection, analysis, and presentation of data. The research subjects were 9 grade 1 students and the class teacher.  The results of the reading ability test show that there are four reading abilities in class 1. As for the first stage, one student is in the red stage or reading closed syllables. Two students are in the blue stage or reading closed syllables. Three students are in the green stage, reading syllables with double vowels and consonants. Four students were able to read sentences.